Image Segmentation Techniques for Remote Sensing Satellite Images. Issue 1 (December 2020) - Bhadoria, Priyanka; Agrawal, Shikha; Pandey, Rajeev
Abstract: The use of satellite imagery has become an integral aspect in the planning of multiple domains that include disaster management and analysis of natural calamity images, snow cover mapping, smart city development, etc. Extraction of urban information like linear features(roads), structured features( buildings, dams, man-made structures), boundaries of water bodies) from satellite images has now become an important area in remote sensing studies. The whole part of a digital image is not useful for a particular purpose hence the image needs to be segmented. Various methods for image segmentation have been proposed but the choice of a particular method depends upon our requirement. Hence it is necessary to have a basic insight of different methods used for remote sensing satellite images. This paper gives a brief explanation of various segmentation methods and the use of these methods on different data sets.